Analisis Faktor-Faktor yang Mempengaruhi Penghindaran Pajak pada Perusahaan Pertambangan Di Bursa Efek Indonesia (BEI) Tahun 2016-2018 - Dwi Fionasari (Politeknik Negeri Bengkalis, 2020)
The purpose of this study is to examine the effect of return on assets, leverage, company size and sales growth on tax avoidance. The population in this study were all mining companies listed on the Indonesia Stock Exchange during the period from 2016 to 2018. The research sample was obtained by using the purposive sampling method, where only 21 mining companies listed on the Indonesia Stock Exchange met all the criteria so that 63 data were obtained, used as a research sample. The data is secondary data. Sources of data in this study were obtained from the Indonesia Stock Exchange website. This study uses multiple regression models to examine the effect of each variable on tax avoidance. Based on the results of the study, it can be concluded that the variable return on assets, leverage, company size and sales growth affect tax avoidance.